OPTIMALISASI POTENSI LOKAL: PEMBERDAYAAN BERBASIS EKONOMI, SOSIAL DAN PENDIDIKAN DI KECAMATAN AIR PURA - Hasanah, Nur; Ravico, Ravico; Bustami, Bustami; rimin, rimin; Siregar, Anggi Desviana; Yati, Risa Marta (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to optimize local potential in the Air Pura District through empowerment based on economic, social, and educational aspects. The program was designed using the Participatory Action Research (PAR) method, emphasizing active participation of the community at every stage, from problem identification and planning to activity evaluation. This participatory approach enables the community to be directly involved in exploring local potential, designing solutions, and taking actions aligned with their needs. The program achieved several key outcomes, including increased community income through diversification of livelihoods based on local potential, strengthened social and cultural values through collaborative activities, and improved education quality through skills training and literacy eradication programs. The success of this program not only brought about positive changes in economic, social, and educational aspects but also established a sustainable empowerment ecosystem. This empowerment model is expected to be replicable in other regions by adapting to their local characteristics.